Impact of climate change in cultural heritage: from energy consumption to artefacts’ conservation and building rehabilitation - Coelho, Guilherme B. A. (2022)
Historic artefacts must be properly preserved if they are to be transmitted to future generations. Indeed, several methodologies and guidelines that aim to safeguard artefacts by limiting the ranges in which the indoor temperature and relative humidity vary exist, which means energy consumption. This paper aims to quantify the energy consumption associated to three different setpoints and respective financial cost, as well as their future trend to demonstrate the positive outcome of passive retrofit measures, since they will be responsible for decreasing the building's energy consumption and mitigating the effects of climate change in artefacts’ preservation. A validated whole-building hygrothermal model of a historic building was used coupled to climate change weather files to obtain the expected future indoor conditions for three types of climates, which were also assessed using a risk-based analysis. The positive potential of passive retrofit measures on the building's energy consumption was shown, but the risk-based analysis showed that the measures performance are not universal since, for example, whilst the selected measures decrease the risk of chemical decay for Seville, they have the contrary behaviour for Oslo. To achieve these goals more than 1400 simulations were run in WUFI®Plus, which took more than 1600 h.